Intersubjectivity and the double : troubled matters - Seitz, Brian, 1954- (New York : Palgrave Macmillan, 2016)
"This book extends philosophy's engagement with the double beyond hi erarchized binary oppositions. Brian Seitz explores the double as a nec essary ontological condition or figure that gets represented, enacted, and performed repeatedly and in a myriad of configurations. Seitz sugge sts that the double in all of its forms is simultaneously philosophy's shadow, its nemesis, and the condition of its possibility. This book ex pands definitions and investigations of the double beyond the confines of philosophy, suggesting that the concept is at work in many other fie lds including politics, cultural narratives, literature, mythology, and psychology. Seitz approaches the double by means of a series of case s tudies and by engaging loosely in eidetic variation, a methodological m aneuver borrowed from phenomenology. The book explores the ways in whic h wide-ranging instances of the double are connected by the dynamics of intersubjectivity"--
The politics of intersubjectivity : representation and the double -- Philosophy's use and abuse of the double : Plato and Kant -- Precisely not me : the deuce in Dostoevsky -- Proximities to death : Freud's arc haic doubles -- The ineluctable double : phenomenology's other -- Epilo gue. Second guessing : emergent doubles.
Includes bibliographical references and index.
Keywords: Intersubjectivity; Dualism; Philosophy